The Merger of Populations as a Revision of Comparison Space: Repercussions for Social Stress and Income Inequality - Oded Stark; Wiktor Budzinski (Institute of Labor Economics (IZA), 2024)
The merger of populations expands the comparison space of incomes. As a result, measures of the income-based social stress and of the income inequality of the constituent populations need to be replaced by new measures. To this end, we develop a procedure for calculating the aggregate social stress and the Gini coefficient of the merged population. We show that to calculate the aggregate social stress when the income distributions of the constituent populations do not overlap, it is sufficient to utilize just three characteristics of the constituent populations: their size, the levels of their aggregate income-based social stress, and their mean income. This result carries over to the calculation of the Gini coefficient of the merged population. We also analyze the extent to which the procedure, applied to cases where the constituent populations do not overlap, can be extended to cases where the income distributions of the constituent populations overlap.
Keywords: D31; D63; F02; F15; 330; income inequality of a merged population; merger of populations; stress of a population; Gini coefficient